A Brief History of Traditional Indian Medicine; in Particular, Yoga and Siddha System of Medicine Part 3A – A Brief on the Knowledge Level of Ancient India and Knowledge Codified Under Yoga, Pertaining to Optimum Health and Maximising Human Potential - Hiramalini Seshadri; Divya Seshadri (NMO Journal)
A brief history of traditional Indian medicine (TIM); in particular, Yoga and Siddha System of Medicine is presented as a four-part series including Part 1 – WHY Indian medicos need to know of the rich medical heritage of Bharat; an eye-opener, Part 2 – Evidence-based Ancient History of India that is Bharat, revisited, Part 3 - A brief on the knowledge level of ancient India and knowledge codified under Yoga, pertaining to optimum health and maximising human potential and Part 4 - A brief on the Siddha system of medicine, including their knowledge level and the Siddha contribution to medical education in the ancient world. Part 3 of the series is divided into two parts. This first part, 3A, covers some examples of the high knowledge level of ancient India in relation to the cosmos, time and mathematics as well as knowledge about conception, embryology and the non-genetic origins of human beings as individuals. It also introduces the limbs of Yoga/Ogam; discusses evidence-based health benefits of Yoga and the use of Dhyana (meditation) to improve quality of modern surgical training in the West. A recent positive Indian experience of the impact of Paraa Vidya (spiritual education) and Yoga on first-year medical students is presented; in addition to Paraa Vidya, providing a basic introduction to TIM will be a further value add; for it will liberate the next generation of medicos from the apologetic colonial mindset and instill confidence and pride in our medical heritage.